Safety and acceptability of clozapine and risperidone in progressive multiple sclerosis: a phase I, randomised, blinded, placebo-controlled trial. Issue 1 (9th July 2020) - La Flamme, Anne C; Abernethy, David; Sim, Dalice; Goode, Liz; Lockhart, Michelle; Bourke, David; Milner, Imogen; Garrill, Toni-Marie; Joshi, Purwa; Watson, Eloise; Smyth, Duncan; Lance, Sean; et al.
Abstract : Objective: Because clozapine and risperidone have been shown to reduce neuroinflammation in humans and mice, the Clozapine and Risperidone in Progressive Multiple Sclerosis (CRISP) trial was conducted to determine whether clozapine and risperidone are suitable for progressive multiple sclerosis (pMS). Methods: The CRISP trial (ACTRN12616000178448) was a blinded, randomised, placebo-controlled trial with three parallel arms (n=12/arm). Participants with pMS were randomised to clozapine (100–150 mg/day), risperidone (2.0–3.5 mg/day) or placebo for 6 months. The primary outcome measures were safety (adverse events (AEs)/serious adverse events (SAE)) and acceptability (Treatment Satisfaction Questionnaire for Medication-9). Results: An interim analysis (n=9) revealed significant differences in the time-on-trial between treatment groups and placebo (p=0.030 and 0.025, clozapine and risperidone, respectively) with all participants receiving clozapine being withdrawn during the titration period (mean dose=35±15 mg/day). Participants receiving clozapine or risperidone reported a significantly higher rate of AEs than placebo (p=0.00001) but not SAEs. Specifically, low doses of clozapine appeared to cause an acute and dose-related intoxicant effect in patients with pMS who had fairly severe chronic spastic ataxic gait and worsening over all mobility, which resolved on drug cessation. Interpretation: The CRISP trial results suggest that patients with pMS may experience increased sensitivity to clozapine and risperidone and indicate that the dose and/or titration schedule developed for schizophrenia may not be suitable for pMS. While these findings do not negate the potential of these drugs to reduce multiple sclerosis-associated neuroinflammation, they highlight the need for further research to understand the pharmacodynamic profile and effect of clozapine and risperidone in patients with pMS. Trial registration number: ACTRN12616000178448.